Incorporated nanoparticles in MOFs thin film for catalysis - Tan, Pei Ting. (2013)
Thin film MOF catalyst is not widely research on only until recent years. In this project, the focus of research will be to incorporate thin film MOF with a mixture of nanoparticles, Pt/Au and Pt/Cu2O to find out the best combination to achieve a novel catalyst. Au and Cu2O both act as sacrificial templates, they are embedded and etched off to create pores and increase the porosity of ZIF-8. However, Cu2O constantly aggregate and dispersed unevenly when embedded and the etching solution corrode both the Cu2O and ZIF-8. Therefore only Au and Pt nanoparticles are selected to be embedded on ZIF-8 for hydrogenation of hexene. Only samples with 5 cycles of nanoparticles displayed catalytic reaction mainly due to the small amount of Pt embedded and the low diffusion rate. Between Pt/ZIF-8 and porous Pt/ZIF-8, porous Pt/ZIF-8 displayed higher catalytic activity due to higher porosity.